2007
DOI: 10.1152/ajpcell.00288.2006
|View full text |Cite
|
Sign up to set email alerts
|

Alloxan-induced diabetes reduces sarcolemmal Na+-K+ pump function in rabbit ventricular myocytes

Abstract: The effect of diabetes on sarcolemmal Na(+)-K(+) pump function is important for our understanding of heart disease associated with diabetes and design of its treatment. We induced diabetes characterized by hyperglycemia but no other major metabolic disturbances in rabbits. Ventricular myocytes isolated from diabetic rabbits and controls were voltage clamped and internally perfused with the whole cell patch-clamp technique. Electrogenic Na(+)-K(+) pump current (I(p), arising from the 3:2 Na(+)-to-K(+) exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…6C). Further, it has been suggested that the Na + -K + pump function is impaired in diabetes [20]. To assess its potential impact, we reduced the Na + /K + pump current in the model by 30%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6C). Further, it has been suggested that the Na + -K + pump function is impaired in diabetes [20]. To assess its potential impact, we reduced the Na + /K + pump current in the model by 30%.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes was induced using techniques adapted from published studies [1315, 20]. A single injection of alloxan monohydrate (140–160 mg/kg body weight) was administered, via the ear vein during brief sedation (via a combination of ketamine/xylazine).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously demonstrated 11 that a switch in the use of these substrates is highly important in certain physiological conditions, such as physiological and pathological pregnancy, which are also characterized by increased levels of endogenous ouabain. 35 This result can be of importance also in other pathological conditions as the sodium pump is regulated in conditions such as hyperglycemia associated with diabetes, 36 and is linked to mediation of the glucose uptake and/or lactate production. Na þ ∕K þ -ATPase was shown to interact with multiple signaling proteins to transmit ouabain signals, 3,37 and several intracellular pathways are known to be implicated in this transmission; namely, ouabain was shown to affect mitochondrial NAD(P)H and ROS generation.…”
Section: Discussionmentioning
confidence: 97%
“…Although this study was performed on patch-clamped, internally perfused myocytes, our previous studies indicate that ANG II also inhibits the pump in isolated intact myocytes and in vivo (17,19,20). We treated rabbits with an angiotensinconverting enzyme inhibitor (ACEI) or an ANG II type I receptor (AT 1 ) antagonist for 1 wk, isolated myocytes, and measured I p .…”
Section: Discussionmentioning
confidence: 99%